Selected indigenous drought tolerant rhizobium strains as promising biostimulants for common bean in Northern Spain - del-Canto, Arantza; Sanz-Saez, Álvaro; Sillero-Martínez, Anna; Mintegi, Eider; Lacuesta, Maite (Frontiers in Plant Science, 2023)
Drought is the most detrimental abiotic stress in agriculture, limiting crop growth and yield and, currently, its risk is increasing due to climate change. Thereby, ensuring food security will be one of the greatest challenges of the agriculture in the nearest future, accordingly it is essential to look for sustainable strategies to cope the negative impact of drought on crops. Inoculation of pulses with biostimulants such as rhizobium strains with high nitrogen fixation efficiency and drought-tolerance, has emerged as a promising and sustainable production strategy. However, some commercial inoculums are not effective under field conditions due to its lower effectiveness against indigenous rhizobium strains in the establishment of the symbiosis. Thus, in the present study, we evaluated the ability to improve drought tolerance in common bean plants of different indigenous rhizobia strains isolated from nearby crop fields in the Basque Country either affected by drought or salinity. The plants in this trial were grown in a climatic chamber under controlled conditions and exposed to values of 30% relative soil water content at the time of harvest, which is considered a severe drought. From the nine bacteria strains evaluated, three were found to be highly efficient under drought (namely 353, A12 and A13). These strains sustained high infectiveness (nodulation capacity) and effectiveness (shoot biomass production) under drought, even surpassing the plants inoculated with the CIAT899 reference strain, as well as the chemically N-fertilized plants. The tolerance mechanisms developed by plants inoculated with 353, A12 and A13 strains were a better adjustment of the cell wall elasticity that prevents mechanical damages in the plasma membrane, a higher WUE and an avoidance of the phenological delay caused by drought, developing a greater number of flowers. These results provide the basis for the development of efficient common bean inoculants able to increase the yield of this crop under drought conditions in the Northern Spain and, thus, to be use as biostimulants. In addition, the use of these efficient nitrogen fixation bacteria strains is a sustainable alternative to chemical fertilization, reducing cost and minimizing its negative impact on environment.